Pitch, tweet, or engage on the street how to practice global public relations and strategic communication - Alaimo, Kara (Routledge, 2021)
"The second edition of Pitch, Tweet, or Engage on the Street offers a modern guide for how to adapt public relations strategies, messages, and tactics for countries and cultures around the globe. Drawing on interviews with public relations professionals in over 30 countries as well as the author's own experience, the book shows how to build and manage a global public relations team, how to practice global crisis communication, and how to practice global public relations on behalf of corporations, non-profit organizations, and governments. It takes readers on a tour of the world, explaining how to adapt their campaigns for Asia-Pacific, Europe, the Middle East, the Americas, and Sub-Saharan Africa. Along the way, readers are introduced to practitioners around the globe and case studies of particularly successful campaigns. This new edition includes updates to country profiles to reflect historical changes in each local context; expanded coverage of social media and the role of influencer engagement; and a brand-new chapter, "Global PR in the Era of Fake News and Filter Bubbles". The book is ideal for graduate and upper-level undergraduate public relations students, as well as practitioners in intercultural markets"-- c Provided by publisher